DNA vaccines for bacterial infections - Simmons, Cameron (2018)
DNA vaccines are an exciting development in vaccine technology which may have a special role in preventing viral infections and as 'theracines' for cancer. Their use in preventing bacterial infections has, by comparison, been less well documented. While it is unlikely that traditional, highly successful and cheap vaccines for diseases such as diphtheria will be replaced by DNA vaccines, naked DNA may be particularly appropriate for preventing bacterial infections where cytotoxic T cells confer protection, or where a Th1 type T cell response mediates resistance. For example, DNA vaccines containing different mycobacterial antigens have been shown to inhibit overt infections by Mycobacterium tuberculosis in rodent models. The use of DNA vaccines in bacterial infections may be complicated by fundamental differences between prokaryotic and eukaryotic genes and gene products, including mRNA stability, codon bias, secondary structures surrounding native start sequences and glycosylation. These problems can be solved by re-synthesis of bacterial genes to produce 'new' sequences which are more highly expressed by eukaryotic cells.